Corpo erótico e prazer: perspectivas da sexualidade na velhice - Oliveira, Helen Keller Frank Conceição Leal de (2017)
Unlike the major socio cultural conception, old age can be an age with as much possibilities as any other, regarding to living experience and sexuality experimentation. However, myths, taboos and prejudices, proper of a socio cultural context, make harder the comprehension of how the experience of pleasure and sexuality is related to the subjects in this phase of life. Based on this assumption, we conducted this research with exploratory character and qualitative approach. We resorted to the theoretical interdisciplinary reference of Social Gerontology, aiming to verify the sexuality on elderly people in it's modus operandi, while dýnamis, which crosses and sets their bodies, forging new cognitive repertories, managements, intensity on socio affective relationships and, wherefore, express how such events forges new meanings on the historicity of the affective bodies through it's narratives and perceptions. The data collection was made from October to September 2016, through interview, following a record of evaluation elaborated by the researcher with five elderly people, attended in Maturity Park "José Dias da Silva", located in the county of Barueri, metropolitan region of São Paulo. It was verified that the five interviewees differ on various aspects on their perspectives on the issues related to sexuality, either by plural experiences of their historicity, or by the subjective issues and singularity of these subjects. Through the perspectives of these subjects, we tried to understand how these relations of sexuality articulate with the relations of power, in this way presenting analytic subsidies for the understanding of the perspectives of these subjects, finding ways to comprehend, analyze and to question this thematic of sexuality in old age. Thus, we conclude with the present research that sexuality is a complex subject non reducible to one single definition, being, however, a multi dimensional phenomenon, expressed on the plural experiences of the subjects, linked to biopsychosocial processes. Thereby each subject develops their own way of experiencing sexuality according to their subjectivity and singularity over their historicity. We comprehend as well that the fields of multiple affection relations, drives, instincts, forces, socio affective relations and it's expressions don't end in any age and can be done through all life if the subjects desires it